TINGKAT KEJADIAN PERARAHAN POSTAPRTUM BERDASARKAN UMUR DAN STATUS GIZI IBU - sugiarti sugiarti (Akademi Kebidanan Griya Husada Surabaya, 2019)
Introduction: The incidence of bleeding in BPS Retno Surabaya in 2015 to 2016 decreased by 1%, then from 2016 to 2017 there was an increase of 1.2%. Although the rate of bleeding is still below the tolerance level according to the East Java Health Office which is 4% in 2007, but the incidence of bleeding in BPS Retno Soepomo Surabaya has increased from 2016 to 2017, this study aims to determine the description of age, and nutritional status mothers give birth to the incidence of HPP. Method: This research is descriptive. The population used was all maternity during the January-June 2018 period with 110 people with a total sample of 110 people selected using non-probability sampling. Secondary data collection from maternal cohorts and delivery reports. The results of the study were made in the form of frequency distribution and cross tabulation. Results: The results showed that the majority of women aged 20 - 35 years (86.36%), good nutritional status (94.54%) The results of cross tabulation showed that mothers with good nutritional status did not experience HPP (98.08%), compared to mothers with underweight nutritional status of 50% HPP. Discussion: the high incidence of HPP due to age and nutritional status. Midwives as health workers should be able to reduce the incidence of HPP by providing various counseling about reproductive age that is safe for pregnancy and childbirth, providing care and IEC adjusted to the nutritional status of the mother.